CEO research orientation, organizational context, and innovation in the pharmaceutical industry. (16th October 2019) - van de Wal, Nino; Boone, Christophe; Gilsing, Victor; Walrave, Bob
Abstract: This study develops and tests a comprehensive framework that explains what, when, and how CEO characteristics influence firms' innovation outcomes in R&D‐intensive industries. Empirical evidence from 109 CEOs from 87 U.S.‐based pharmaceutical firms over the period 2001–2013 reveals that research‐oriented CEOs – those with ability and motivation for science and technology – increase their firms' innovation outcomes. The results indicate that the CEO–innovation relationship strongly depends on the extent of CEOs' managerial discretion, which is shaped by the organizational context. We contribute to a more comprehensive understanding of the role of CEOs in firms´ innovation performance differentials.